Genetic screens in intestinal organoid (mini-gut) culture using CRISPR-Cas-9 System and studying the role of FBXL5 in colorectal cancer cells - Jinks, Nicholas (2022)
Current in vitro research methods are often difficult to translate into successful gene(s) functional and clinical applications. Immortalised cell lines are monocellular, 2-dimensional and do not accurately encapsulate the in vivo microenvironment, while in vivo animal models are often impractical, prohibitively expensive and ethically contentious. As such, novel in vitro experimental models are required to facilitate research and improve translatability, particularly in colorectal cancer, which demonstrates great genetic and phenotypic heterogeneity. Recently, methods for the in vitro culture of three-dimensional (3D) derived “organoids” have been established, which faithfully reproduce the genetic, proteomic and pharmacological characteristics of their original tissue. Organoids present the opportunity to elucidate molecular mechanisms underlying functional genetic modelling, personalised medicine and drug discovery in vitro, thereby replacing and reducing the use of in vivo animal models.